Long-period structure in Cu–Pd–Me and Ti–Al–Me metallic alloys - Morozov M. M. Mikhail Mikhaylovich; Potekaev A. I.; Klopotov A. A. Anatoly Anatoljevich; Markova T. N. Tatjyana Nikolaevna; Klopotov V. D. Vladimir Dmitrievich (2015, 2015)
Title screen